Direct and indirect reciprocity among individuals and groups. (February 2022) - Romano, Angelo; Saral, Ali Seyhun; Wu, Junhui
Abstract: Direct and indirect reciprocity are two fundamental mechanisms that promote prosocial behavior within groups and across societies. Here, we review recent work that illustrates how a (direct and indirect) reciprocity framework can illuminate our understanding of several factors related to prosocial behavior — namely group membership, gossip, and third-party punishment. We propose that each of these factors can promote prosocial behavior via proximate psychological mechanisms related to direct and indirect reciprocity: reputational concern, expectations, and anticipation of future interaction. Finally, we discuss the implications of adopting such a framework and highlight a number of avenues for future research. Highlights: Behavioral experiments support the predictive power of direct and indirect reciprocity. Reciprocity helps explain the effects of group membership, gossip, and third-party punishment on prosocial behavior. Group membership serves as a heuristic for expected partner's prosocial behavior and anticipated future interactions. Gossip promotes prosocial behavior via an increased concern for reputation and expected partner's prosocial behavior. Costly third-party punishment serves to deter potential defectors and maintain a positive reputation.